TINJAUAN YURIDIS TENTANG PERBUATAN PIDANA SECARA BERLANJUT DI PERUSAHAAN SEBAGAIMANA DIATUR DAN DIANCAM PASAL 374 KUHP Jo. PASAL 64 AYAT (1) KUHP - Suraya suraya (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTApplication of Article 374 of the Criminal Code in conjunction with Article 64 paragraph ( 1 ) of the Criminal Code by the judges in the criminal case No. . 15/Pid.B/1999/PN.Smda is right , but the length of the sentence imposed by the judges apart from the things that burden and lighten the punishment meted out to the perpetrators of criminal acts of fraud committed company goods respectively - were . In connection with the criminal case that the defendant was sentenced to five (5 ) months , the authors suggest a very light sentence . In connection with the problems of classification of criminal acts of fraud as set forth and Article 374 of the Criminal Code punishable in conjunction with Article 64 paragraph ( 1 ) of the Criminal Code is a criminal act of fraud by weighting . As a result of legal action against the perpetrators of criminal fraud by weighting as provided for in Article 374 of the Criminal Code is imprisonment for - length 5 ( five ) years . While the criminal case No. verdict . 15/Pid.B/1999/PN.Smda as described above , the perpetrators of criminal acts of fraud committed company goods respectively - were included in the classification of criminal acts by weighting with imprisonment for 5 ( five ) months . Therefore , those who in the classification of criminal acts of fraud by weighting , the deed should be terminated by a pretty severe punishment